Humor e intertextualidad en la cuentistica de Igor Delgado Senior - Pifano, Diana (University of Ottawa (Canada), 2009)
During the 1980s and 1990s, Venezuela struggled through a profound economic, political and social crisis that resulted in popular uprisings, the collapse of some of the nation's largest financial institutions and the trial and sentence of President Carlos Andres Perez for the embezzlement of public funds. It was during this time, that author and humorist Igor Delgado Senior (1942) published three anthologies of short stories: Relatos de Tropicalia (1985), Sub-America (1992) and Sexo sentido y otros cuentos (1998). The stories collected in those volumes reflect and comment on the events of those difficult years, but they do so through the discourse of humour. The purpose of this study is to delineate the most significant qualities of the author's narrative and to describe the critical commentary he puts forth in these texts. In order to do so, it will be essential to carry out a comprehensive analysis of these stories, that is, an analysis that examines the relationship between humour and literature in these texts. Proceeding from the point of view of the reader, we shall explore how humour is woven into the fabric of these stories and how it contributes to the construction of literary meaning through an intertextual process that has its basis in parodic representation. By setting forth a methodology for integrating the study of humour to the framework of literary analysis, I describe the communicative role of humour in Delgado Senior's short stories and reflect on its social and critical values.
Keywords: Literature, Modern.; Literature, Latin American.